2022
DOI: 10.1101/2022.11.16.516826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell response to extracellular matrix energy dissipation outweighs rigidity sensing

Abstract: The mechanical properties of the extracellular matrix (ECM) determine cell differentiation, proliferation and migration through mechanoresponsive proteins including YAP. However, how different mechanical signals cooperate, synergize or compete to steer cell behavior remains poorly understood. Here, we have examined competition between the two major ECM mechanical cues, i.e. rigidity, which activates cell mechanosensing, and viscous energy dissipation, which reduces stiffness blunting cell mechanotransduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Such behavior is called as ‘cruse of dimensionality [ 103 ]. During the training of the data, when the number of neurons increases, the computational of the network becomes complex; such a scenario during the training of data is known as ‘computational efficiency [ 104 ]. To estimate the suitable number of neurons, it is significant to strike a balance between the model’s complexity and the data’s generalisation.…”
Section: Resultsmentioning
confidence: 99%
“…Such behavior is called as ‘cruse of dimensionality [ 103 ]. During the training of the data, when the number of neurons increases, the computational of the network becomes complex; such a scenario during the training of data is known as ‘computational efficiency [ 104 ]. To estimate the suitable number of neurons, it is significant to strike a balance between the model’s complexity and the data’s generalisation.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, natural tissues and extracellular matrices can dissipate forces under stress, which depends on the nature of the crosslinks, slip and slide phenomena, the release of polymeric entanglements, and protein unfolding. [1,15,17,[29][30][31][32][33] Furthermore, under tension or compression, dissipation occurs due to the flow of water into or out of the network within the extracellular matrix resulting from volume changes (poroelasticity). [1] In the present work we start comparing three agarose samples characterized by a different methylation pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Viscous energy dissipation can be determined under loading/unloading stress-strain cycles (hysteresis area) or by calculating the loss tangent through rheometry. [2,10,15] Soft but also stiffer tissues exhibit viscous moduli that are generally 10% to 20% of their elastic moduli, i.e., loss tangents in the range of 0.1-0.2. Apart from viscous energy dissipation, it has recently been shown that cells exhibit elastic energy-sensing that affects important biological functions mediated by the same molecular clutch machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies could implement depth-resolved viscoelastic analysis and include the possibility of layer delamination, a feature already present in ALVA that wasn't explored in this work. The first aspect is particularly crucial, as recent studies have shown how cellular response to the viscosity of its microenvironment outweighs rigidity sensing [49,50].…”
Section: Discussionmentioning
confidence: 99%